Inequalities Applicable to Mixed Volterra-Fredholm Type Integral Equations - Pachpatte, B. G. (Sarajevo Journal of Mathematics, 2024)
In this paper we establish some new integral inequalities with explicit estimates which can be used as tools in the study of some basic properties of solutions of mixed Volterra-Fredholm type integral equations. Discrete analogues of the main results and some applications of one of our results are also given. 2000 Mathematics Subject Classification. 65R20, 45G10